ETHICAL AND TEACHING CULTURE: Concept and Logical Framework Analysis (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
The article gives a brief overview of the development of ideas about ethics and pedagogical culture, marked structural components and concluded that the task of modern higher education is to prepare specialists meeting iconative style within the environment of professional interaction subjects. Ethical and teaching culture: concept and logica framework analysis Pedagogical culture, ethical - pedagogical culture, iconative style, interaction of subjects, environment of professional interaction.